2019
DOI: 10.1186/s43044-019-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between prediabetes and coronary artery disease severity in patients undergoing elective coronary angiography

Abstract: Background: Diabetes is a chronic disease that is responsible for a high rate of morbidity and mortality which can be attributed to atherosclerosis and cardiovascular disease. Diabetes is heralded by prediabetes which not only indicates a higher risk of developing diabetes but also increases the burden of cardiovascular disease. The objective was to observe the effect of prediabetes on the severity of coronary artery disease in patients undergoing elective coronary angiography. Seven hundred and thirty-one pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…We assessed the incidence of atherosclerosis CAD and its burden in prediabetes and its impact on coronary vessels and CAG outcomes. In our study, 110 (24.01%) patients had prediabetes; the prevalence of men was high in all groups, while in other studies, women were predominant in the diabetes group [10,11]. The frequency of prediabetes with smoking and CAG + PCI/PTCA is higher in the prediabetes group, similar to the other studies conducted by Muhammed et al [10].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We assessed the incidence of atherosclerosis CAD and its burden in prediabetes and its impact on coronary vessels and CAG outcomes. In our study, 110 (24.01%) patients had prediabetes; the prevalence of men was high in all groups, while in other studies, women were predominant in the diabetes group [10,11]. The frequency of prediabetes with smoking and CAG + PCI/PTCA is higher in the prediabetes group, similar to the other studies conducted by Muhammed et al [10].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 110 (24.01%) patients had prediabetes; the prevalence of men was high in all groups, while in other studies, women were predominant in the diabetes group [10,11]. The frequency of prediabetes with smoking and CAG + PCI/PTCA is higher in the prediabetes group, similar to the other studies conducted by Muhammed et al [10]. Our study results found no statistical significance in smoking among the groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Patients with intermediate hyperglycemia of HbA1c ranging from 6.0 to 6.5% were defined as prediabetic according to the World Health Organization (WHO) [ 8 ]. Compared with normoglycemic individuals, prediabetes is related to a high atherosclerotic burden and the number of vessels affected in Ahmed’s study [ 9 ]. Another study illustrated that patients with prediabetes have a significantly increased long-term risk of cardiovascular disease after PCI [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the prediabetic patients do not receive timely diagnosis and treatment, about 5-10% of them will rapidly progress to the stage of diabetes, and the rest will gradually develop diabetes over the next 5 years. In the meantime, the incidence and severity of diseases such as coronary artery disease, heart failure, hypertension and retinopathy in patients with prediabetes are aggravated with more obvious blood glucose fluctuation, thus seriously affecting their quality of life [3][4][5][6]. As a result, timely diagnosis and intervention for diabetics can postpone the progression of prediabetes to diabetes and lower the risk of related complications, which is critical for both society and patients.…”
Section: Introductionmentioning
confidence: 99%